Prevention and management of secondary central nervous system lymphoma - Bobillo, Sabela; Khwaja, Jahanzaib; Ferreri, Andrés J.M.; Cwynarski, Kate (Haematologica (Roma), 2023)
Secondary central nervous system (CNS) lymphoma (SCNSL) is defined by the involvement of the CNS, either at the time of initial diagnosis of systemic lymphoma or in the setting of relapse, and can be either isolated or with synchronous systemic disease. The risk of CNS involvement in patients with diffuse large B-cell lymphoma is approximately 5%; however, certain clinical and biological features have been associated with a risk of up to 15%. There has been growing interest in improving the definition of patients at increased risk of CNS relapse, as well as identifying effective prophylactic strategies to prevent it. SCNSL often occurs within months of the initial diagnosis of lymphoma, suggesting the presence of occult disease at diagnosis in many cases. The differing presentations of SCNSL create the therapeutic challenge of controlling both the systemic disease and the CNS disease, which uniquely requires agents that penetrate the blood-brain barrier. Outcomes are generally poor with a median overall survival of approximately 6 months in retrospective series, particularly in those patients presenting with SCNSL after prior therapy. Prospective studies of intensive chemotherapy regimens containing high-dose methotrexate, followed by hematopoietic stem cell transplantation have shown the most favorable outcomes, especially for patients receiving thiotepa-based conditioning regimens. However, a proportion of patients will not respond to induction therapies or will subsequently relapse, indicating the need for more effective treatment strategies. In this review we focus on the identification of high-risk patients, prophylactic strategies and recent treatment approaches for SCNSL. The incorporation of novel agents in immunochemotherapy deserves further study in prospective trials.